Development of six-degree of freedom strapdown terrestrial INS algorithm - Baghdad Science Journal (مجلة بغداد للعلوم)
Many of accurate inertial guided missilc systems need to use more complex mathematical calculations and require a high speed processing to ensure the real-time opreation. This will give rise to the need of developing an effcint